Association Between Admission Mean Arterial Pressure and the Development of Contrast-Associated Nephropathy Within the First 72 Hours in Patients With NSTEMI - Bulu, Aykut; Işık, Ömer; Kobat, Mehmet Ali (Eskişehir Şehir Hastanesi [EN], 2026)
Introduction: Contrast-associated acute kidney injury (CI-AKI) is a frequent and clinically important complication after percutaneous coronary intervention (PCI), particularly in hemodynamically unstable patients with non–ST-elevation myocardial infarction (NSTEMI). Mean arterial pressure (MAP) is a key determinant of renal perfusion, yet the impact of admission MAP on CI-AKI development in NSTEMI patients undergoing PCI has not been clearly established. To investigate the relationship between admission MAP and the development of CI-AKI within the first 72 hours after PCI in patients with NSTEMI. Methods: This single-center, retrospective observational study included 150 consecutive patients hospitalized with NSTEMI who underwent PCI between January and December 2025. Admission systolic and diastolic blood pressures were obtained from emergency department triage records and MAP was calculated using the standard formula (MAP = [SBP + 2×DBP]/3). CI-AKI was defined according to KDIGO criteria as an increase in serum creatinine ?0.3 mg/dL or ?50% from baseline within 72 hours after contrast exposure. Patients were divided into two groups: those who developed CI-AKI (n=62, 41.3%) and those who did not (n=88, 58.7%). Non-parametric tests and Spearman correlation analysis were used. Results: The overall mean MAP was 88.99±27.44 mmHg. Patients who developed CI-AKI had significantly lower admission MAP compared with those without CI-AKI (60.33±3.95 vs. 109.18±16.76 mmHg; p

Giriş: Kontrast ilişkili akut böbrek hasarı (Kİ-ABH), perkütan koroner girişim (PKG) sonrası sık görülen ve mortalite ile morbiditeyi artıran önemli bir komplikasyondur. Ortalama arter basıncı (OAB), renal perfüzyonun temel belirleyicilerinden biridir; ancak PKG uygulanan non-ST elevasyonlu miyokart enfarktüsü (NSTEMI) hastalarında başvuru OAB’sinin Kİ-ABH gelişimi üzerine etkisi net olarak ortaya konmamıştır. NSTEMI nedeniyle PKG uygulanan hastalarda başvuru anındaki ortalama arter basıncı ile işlemi takip eden ilk 72 saat içinde gelişen Kİ-ABH arasındaki ilişkinin değerlendirilmesi amaçlandı. Yöntemler: Bu tek merkezli, retrospektif gözlemsel çalışmaya Ocak–Aralık 2025 tarihleri arasında NSTEMI tanısıyla yatırılarak PKG uygulanan ardışık 150 hasta dahil edildi. Başvuru sistolik ve diyastolik kan basıncı değerleri acil servis triyaj kayıtlarından alındı ve standart formül kullanılarak OAB hesaplandı (OAB = [SKB + 2×DKB]/3). Kİ-ABH, KDIGO kriterlerine göre, kontrast maruziyetini takiben 72 saat içinde serum kreatinin düzeyinde ?0,3 mg/dL artış veya başlangıca göre ?%50 relatif artış olarak tanımlandı. Hastalar Kİ-ABH gelişen (n=62; %41,3) ve gelişmeyen (n=88; %58,7) olmak üzere iki gruba ayrıldı. İstatistiksel analizlerde non-parametrik testler ve Spearman korelasyon analizi kullanıldı. Bulgular: Tüm kohortun ortalama OAB değeri 88,99±27,44 mmHg idi. Kİ-ABH gelişen hastalarda başvuru OAB’si, gelişmeyenlere göre anlamlı derecede daha düşük saptandı (60,33±3,95 vs. 109,18±16,76 mmHg; p
NSTEMI Hastalarında Başvuru Ortalama Arteriyel Basınçları ile İlk 72 Saat İçinde Gelişen Kontrast İlişkili Nefropati Arasındaki İlişki
Keywords: Cardiovascular Medicine and Haematology (Other); Kardiyovasküler Tıp ve Hematoloji (Diğer); Nefroloji; Nefroloji